The Role of Systemic Immune-Inflammation Index in Severe Bicuspid Aortic Stenosis - Süygün, Hakan (The European Research Journal, 2026)
Objectives: Bicuspid aortic valve (BAV) is the most common congenital cardiac abnormality and often leads to severe aortic stenosis (AS) at a younger age compared to tricuspid valves. Inflammation plays a key role in the pathogenesis of AS. This study aimed to investigate the association between the Systemic Immune-Inflammation Index (SII) and disease severity in patients with severe BAV-AS. Methods: In this retrospective observational study, 76 patients with severe BAV-AS and 76 age- and sex-matched controls without AS were included. Routine laboratory data and transthoracic echocardiographic parameters were recorded. SII was calculated as platelet count × neutrophil count / lymphocyte count. The severity of AS was determined by aortic valve area (AVA) and mean transvalvular gradient. Correlation analyses, Receiver Operating Characteristic (ROC) curve, and logistic regression were used to assess the relationship between SII and AS severity. Results: The BAV-AS group had significantly higher SII values compared to controls (median: 931.7 vs. 534; P<0.001). SII showed a moderate inverse correlation with AVA (r = –0.547) and a positive correlation with mean gradient (r=0.535). The optimal SII cut-off for predicting severe BAV-AS was 691 (AUC=0.790), with sensitivity of 71.1% and specificity of 77.6%. Multivariate analysis identified SII as an independent predictor of severe BAV-AS (OR: 3.841, 95% CI: 1.395-10.576; P=0.009). Conclusions: SII is significantly elevated in patients with severe BAV-AS and may serve as a useful inflammatory biomarker for disease burden. Further studies are needed to confirm its utility in clinical decision-making.